The Effect of Audit Delay on Information Asymmetry with Audit Opinion in Indonesian Listed Companies - Sunaryo, Dede; Erdawati, Lena; Khikmah, Siti Noor; Simanjuntak, Daniel Nicson (Eastasouth Institute, 2026)
This study aims to examine the effect of audit delay on information asymmetry and audit opinion in public companies in Indonesia. Audit delay, defined as the time lag between the fiscal year-end and the issuance of the auditor’s report, is considered an important factor influencing the timeliness and reliability of financial reporting. This research adopts a quantitative approach using primary data collected from 35 respondents through structured questionnaires measured on a Likert scale. The data were analyzed using SPSS version 25, including descriptive statistics, validity and reliability tests, classical assumption tests, and multiple regression analysis. The results indicate that audit delay has a significant positive effect on information asymmetry, meaning that longer delays increase the information gap between management and stakeholders. In addition, audit delay also has a significant effect on audit opinion, suggesting that prolonged audit processes are associated with a higher likelihood of receiving less favorable audit opinions. The coefficient of determination shows that audit delay explains 51.1% of the variation in information asymmetry and 42.7% of the variation in audit opinion. These findings highlight the importance of timely audit completion in enhancing transparency, reducing uncertainty, and improving the credibility of financial reporting. The study contributes to the literature by providing empirical evidence from Indonesia and offers practical implications for companies, auditors, and regulators in improving audit efficiency and reporting quality.